2007
DOI: 10.1002/cbic.200600535
|View full text |Cite
|
Sign up to set email alerts
|

Protonation Patterns in Tetracycline:Tet Repressor Recognition: Simulations and Experiments

Abstract: Resistance to the antibiotic tetracycline (Tc) is regulated by its binding as a Tc:Mg2+ complex to the Tet Repressor protein (TetR). Tc:TetR recognition is a complex problem, with the protein and ligand each having several possible conformations and protonation states, which are difficult to elucidate by experiment alone. We used a combination of free-energy simulations and crystallographic analysis to investigate the electrostatic interactions between protein and ligand and the possible role of induced fit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 59 publications
4
86
0
Order By: Relevance
“…When it binds, the H 6 proton is released, giving a Tc − :Mg 2+ complex. We found that tetracycline prefers an extended, zwitterionic state both in solution and in complex with the TetR protein, 7 the elongation factor EF-Tu (AA & TS, unpublished results) and the ribosome. 9 Tc is thus preorganized for binding.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…When it binds, the H 6 proton is released, giving a Tc − :Mg 2+ complex. We found that tetracycline prefers an extended, zwitterionic state both in solution and in complex with the TetR protein, 7 the elongation factor EF-Tu (AA & TS, unpublished results) and the ribosome. 9 Tc is thus preorganized for binding.…”
Section: Introductionmentioning
confidence: 87%
“…Only the extended Tc conformation is found. In our previous study 7 we showed by MD free energy methods that Tc bound to TetR is in its zwitterionic state. In the ribosome 9 and elongation factor Tu (AA & TS, unpublished results), tetracycline was also found in its zwitterionic form, suggesting that only this, zwitterionic-extended form of tetracycline is relevant in biological complexes.…”
Section: Protonation States and Conformations In The Ccdb And The Pdbmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the ribosome and the solution transformations were modeled as rearrangements of atomic charges on the imidazole group. See references Simonson et al (2004) and Aleksandrov et al (2007) for details. The systems were solvated in a 70 Å box of water, and periodic boundary conditions were imposed so that the entire box was replicated periodically in all directions.…”
Section: Alchemical MD Free-energy Simulationsmentioning
confidence: 99%
“…Those of most residues were straightforward to deduce, but there was some uncertainty about the δ-protonation of His85 in the ribosome complex, which is crucial for reaction. To resolve this, we utilized MD free-energy simulations (Sham et al 1997;Simonson et al 2004;Aleksandrov et al 2007) to calculate the free energy of protonation from the thermodynamic cycle shown in Figure 2. To effect the protonations of the histidine in solution and in the ribosome complex, we performed a series of MD simulations in which the neutral and charged forms of His85 were reversibly transformed in both directions.…”
Section: His85 Protonation Free-energy Simulationsmentioning
confidence: 99%